Induction of Pyroptosis: A Promising Strategy for Cancer Treatment - Wang, Lei; Qin, Xiaowei; Liang, Jianmin; Ge, Pengfei (Frontiers in Oncology, 2021)
Pyroptosis, a lytic pro-inflammatory type of programmed cell death, has been widely studied in diverse inflammatory disease models. Membrane perforation and cell swelling induced by cleaved gasdermin family members is the main characteristic of pyroptosis. Emerging evidence has revealed a complicated relationship between pyroptosis and cancer. On one hand, as inflammatory cell death, pyroptosis provides a comfortable environment for tumor proliferation. On the other hand, excessive activation of pyroptosis can inhibit the development of tumor cells. In this review, we first made a summary of the latest progress about the molecular mechanism of pyroptosis. Then members from gasdermin family, the central molecules of pyroptosis which formed pores on the cell membrane, were highlighted. In the second part of this review, we summarized drugs that induced pyroptosis in different tumors and their concrete mechanisms based on recent literature reports. In the final section, we discussed several hotspots in pyroptosis and cancer therapy, which will point out the direction of sequent research. In brief, inducing pyroptosis in cancer cells is a promising strategy for cancer therapy.